2006
DOI: 10.1109/tcbb.2006.11
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Analysis of Constitutive Exocytosis in Epithelial Cells

Abstract: Exocytosis is an essential cellular trafficking process integral to the proper distribution and function of a plethora of molecules, including transporters, receptors, and enzymes. Moreover, incorrect protein targeting can lead to pathological conditions. Recently, the application of evanescent wave microscopy has allowed us to image the final steps of exocytosis. However, spatio-temporal analysis of fusion of constitutive vesicular traffic with the plasma membrane has not been systematically performed. Also, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 28 publications
2
44
0
Order By: Relevance
“…Since fusion events often clustered in small domains of the membrane, which we call hotspots, we tested whether Sec8-depletion causes a randomization of the locations of fusion events. We modeled the exocytic process as a spatial point process, ie, a random variable producing points at random locations representing the location of events (42). A homogenous Poisson process is a completely random point process, in which the number of events in nonoverlapping spatial regions is independent and the probability of an event is the same at all locations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since fusion events often clustered in small domains of the membrane, which we call hotspots, we tested whether Sec8-depletion causes a randomization of the locations of fusion events. We modeled the exocytic process as a spatial point process, ie, a random variable producing points at random locations representing the location of events (42). A homogenous Poisson process is a completely random point process, in which the number of events in nonoverlapping spatial regions is independent and the probability of an event is the same at all locations.…”
Section: Resultsmentioning
confidence: 99%
“…We used total internal ref lection f luorescent (TIRF) microscopy (38)(39)(40)(41)(42) in combination with RNAi against Sec8, the most frequently studied exocyst subunit. As a next step, we capitalized on the existence of a dominant negative mutant of the Exo70 exocyst subunit, which allowed us to test the importance of the exocyst directly in migrating cortical neurons during embryonic development.…”
mentioning
confidence: 99%
“…Total Internal Reflexion Fluorescence [4] microscopy based on the properties of evanescent waves propagation at the interface between two media with sufficiently different refractive indexes, is certainly the method of choice. This widely used approach demonstrated that transient fluorescence concentrations can occur close to or at the plasma membrane, suggesting that they may correspond to membrane sites specialized in endocytosis or exocytosis [5]. Among diverse molecular behaviors reported by previous microscopy studies on this molecular model, plasma membrane concentration of fluorescently tagged proteins give rise to sudden spot appearance and/or disappearance.…”
Section: Biological Model Experimental Setup and Image Acquisitionmentioning
confidence: 83%
“…For instance, in [193], a point process modeling is proposed in order to characterize some properties of the endo/exocytosis process such as the presence of clusters from detecting spots. Generally, the manual detection of objects over a cluttered time-varying background is very tedious especially in 3D and subjective.…”
Section: B Intracellular Traffic Analysis and Molecular Mobilitymentioning
confidence: 99%
“…More specifically, some methodologies can be considered for the automatic detection of appearing and vanishing spots of fluorescently labelled clustered molecules in wide-field (WF) and TIRF microscopy images [193], [190]. The difficulty is to distinguish motions due to trafficking from the appearing and vanishing spots.…”
Section: Spatio-temporal Detectionmentioning
confidence: 99%